Obstetrical nursing and health education: contributions to the experience of process of parturition - Jacqueline Silveira de Quadros; Thamiza Lauriany da Rosa dos Reis; Juliana Silveira Colomé (Rev Rene)
Objective: to understand the contributions of obstetrical nursing to health education activities aimed at the parturition process. Methods: qualitative research conducted with ten hospitalized puerperal women who had vaginal delivery in a maternity ward. Results: two categories emerged from the data of this research: Weaknesses of prenatal care for pregnant women and The obstetrical nurse as potentiator of humanized care. Conclusion: obstetrical nursing, through educational work, strives to promote a reframing of the process of parturition, rescuing parturition as a physiological process, and emphasizing the use of natural resources in the evolution of labor and delivery.